Entrepreneurship Education in Developing People’s Economy - Irmawita, Irmawita (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2019)
The various impacts that have been taken in the era of globalization and increasingly widespread transformation will have positive and negative impacts. Various potentials faced, both natural resources and human resources must be a priority to be developed, especially by the Study Program of Non Formal Education as one of the educational institutions that must be a solution for an increasingly developing age. One way that can be taken to develop human resources, especially the PLS study program is through student self-development towards the cultivation of entrepreneurial spirit in aspects of life. It is very important to do outside school education that is closely related to education for the community to continue to be a pioneer in the development people's economy which has an entrepreneurial spirit, devotion and conduct economic business through koperasi and small and medium enterprises so that intact human resources can be built independent, productive and able to become the hope of the nation that responds to the flow of globalization with various challenges. The challenge of globalization towards self-reliance and productive endeavors for students of study programs outside of school is a shared hope towards people's economy and the transparent world of work and accountability.